MODEL SISTEM INFORMASI MONITORING PERKULIAHAN FAKULTAS TEKNIK UNIVERSITAS SEMARANG BERBASIS WEB - Derman, Derman; Harmini, Harmini (Elektrika, 2018)
The development of Information Technology is increasingly demanding that Higher Education to provide information quickly to meet the needs of Information and Monitoring Course for Lecturers, Students and Admin staff. This study aims to design a Model Information System and Monitoring Course at the Faculty of Engineering, University of Semarang Web-based. Coverage includes lecture planning, lecturing, evaluation of lecturing, control of lecturing and improvement of lecture planning. This research produces an application of Information System and Monitoring model of lecturing which aims to facilitate and accelerate the preparation of time, room and course schedule and ease in monitoring the attendance status of lecturers in class either to students or other parties in real time without having to come to campus check board information . The contribution of this research results will greatly affect the application of science and technology for higher education institutions and to realize the development of Faculty of Engineering Semarang University as a leading Faculty in 2023. The method used is dynamic priorities method which prioritizes the process that has the highest priority and is able to respond to changes in the system environment operate. Modeling the system using XAMPP package in which integrated MySQL module for database purposes, PHP for management of information systems, and Apache for simulation purposes. The results showed the implementation of the application of Information Systems Monitoring System Lectures Faculty of Engineering, University of Semarang goes well.